2014
DOI: 10.1016/j.cellsig.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulatory mechanisms of the human ferritin gene by hypoxia and hypoxia mimetic cobalt chloride at the transcriptional and post-transcriptional levels

Abstract: Cobalt chloride has been used as a hypoxia mimetic because it stabilizes hypoxia inducible factor-1α (HIF1-α) and activates gene transcription through a hypoxia responsive element (HRE). However, differences between hypoxia and hypoxia mimetic cobalt chloride in gene regulation remain elusive. Expression of ferritin, the major iron storage protein, is regulated at the transcriptional and posttranscriptional levels through DNA and RNA regulatory elements. Here we demonstrate that hypoxia and cobalt chloride reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…This indicates that the targets of increased cobalt chloride and decreased oxygen (probably through the generation of reactive oxygen species; Bell et al 2007) are separable. These results align with previous findings that have demonstrated differential effects brought about by cobalt chloride and hypoxia treatments (Vengellur et al 2005;Huang et al 2014a).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This indicates that the targets of increased cobalt chloride and decreased oxygen (probably through the generation of reactive oxygen species; Bell et al 2007) are separable. These results align with previous findings that have demonstrated differential effects brought about by cobalt chloride and hypoxia treatments (Vengellur et al 2005;Huang et al 2014a).…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that the targets of increased cobalt chloride and decreased oxygen (probably through the generation of reactive oxygen species; Bell et al 2007) are separable. These results align with previous findings that have demonstrated differential effects brought about by cobalt chloride and hypoxia treatments (Vengellur et al 2005;Huang et al 2014a).Precisely how either insult affects BLMP-1 to alter transcriptional output in C. elegans will require more investigation; however, it is intriguing to note that hypoxia-initiated and BLMP-1-dependent increases in histone acetylation at the F45D3.4 promoter may point to a shared response pathway that includes the prolongevity factor LIN-40, one of the other two positive hits identified in our screen. LIN-40 is an essential component of the nucleosome remodeling deacetylase (NuRD) complex (Johnsen and Baillie 1991;Solari et al 1999) that was recently shown to promote stress resistance and longevity in a circuit that involves the germline and the insulin pathway (Zimmerman and Kim 2014).…”
supporting
confidence: 83%
“…Similar effects have been seen in macrophages, where INF-γ activated U937 cells treated with TNF-α also induced FTH mRNA expression (7). Nrf2, a basic leucine zipper transcription factor that regulates antioxidant protein expression, is recruited to the antioxidant responsive element (ARE) in the FTH promoter region, stimulating its transcription (41). IL-1β has also been shown to have a direct effect on a 5′ Fig.…”
Section: Heavy Chain Ferritin During Inflammationmentioning
confidence: 56%
“…CoCl 2 -treated cells were used as a model of chemical hypoxia-induced injury; however, there are several other effects of hypoxia that are not achieved by treatment with CoCl 2 . For example, CoCl 2 may stabilize the expression of hypoxia-inducible factor 1α (HIF-1α) (46,47). Second, the mechanisms underlying the antioxidant and anti-apoptotic properties of α-MG are not fully elucidated, and continued research is required in the future.…”
Section: Discussionmentioning
confidence: 99%